Macroanatomic investigations on the innervation of the tongue in anatolian buffaloes - Vural Özdemir; Sadullah Bahar; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
The aim ol this study was to investigate the origines, courses and innervation areas of the cranial nerves, innervating the tongue in Anatolian Buffaloes, The lingual nerve terminated in the rostral two thirds of the tongue. The chorda tympani joined to Ihe lingual nerve. The glossopharyngeal nerve stemmed from the medulla oblongata, then, dispersed in the caudal one third of the tongue. The hypoglossal nerve scattered in the tongue muscles after arising from the medulla oblongata.